A novel correlation adaptive receiver structure for high speed transmissions in ultra wide band systems with realistic channel estimation (2009)
Impulse radio ultra wide band (UWB) communications require robust receivers; typically Rake receivers are required to capture a large number of resolvable paths, (even hundred of paths), so large number of correlators are needed; otherwise, adaptive receivers use complex filters and channel estimation algorithms. Therefore, traditional Impulse Radio receivers demand non-practical implementation structures. In this paper we propose a novel correlation-adaptive receiver structure with low complexity for indoor high speed ultra wide band systems. This novel structure combines correlation characteristics from rake receivers with recursive filters from adaptive receivers. The receiver includes a low complexity recursive channel estimation filter capable of estimating hundreds of channel impulse responses, and a single filter-correlation filter used for coherent bit demodulation. Furthermore, we derive by simulations the bit error rate for high density multipath environments for several Impulse Radio modulations like TH-PPM, DS-BPSK and TH-BPSK and we compare the performance of the proposed structure with typical Rake receivers. © 2009 IEEE.